(untitled) - Food and Agriculture Organization of the United Nations (Rome, 2007)
People-centred approaches, diversification and enterprise development, people's participation in policy-making, access to natural resources, land rights, access of the poor to forest resources, natural resource conflict management-Training materials.
Keywords: Sustainable development,Rural development,Phát triển bền vững,Phát triển nông thôn